Giving stakeholders a voice in governance: Biodiversity priorities for New Zealand's agriculture. Issue 2 (29th November 2021) - MacLeod, Catriona J.; Brandt, Angela J.; Collins, Kevin; Dicks, Lynn V.
Abstract: Mainstreaming biodiversity across government and society is recognised by international policy as critical to achieving positive conservation outcomes. With 'participatory governance' increasingly being applied to achieve collective action in conservation, there are growing calls to critically review such processes to capture their complexity and manage for emergent outcomes. This paper critically reviews a case study, aiming to give a broad range of stakeholders a voice in setting biodiversity priorities for New Zealand's agricultural landscape, in relation to four principles for knowledge co‐production in sustainability: context‐based, pluralistic, goal‐orientated and interactive. Aiming to facilitate an inclusive but rapid participation process, while not overburdening those willing to participate, three pathways for engagement were offered. Stakeholder participants were recruited from public, private and civic sectors involved in managing New Zealand's farmland biodiversity. An initial scoping exercise helped elevate biodiversity groups and management actions distinct to New Zealand's social and environmental context. Online surveys then gave stakeholders, from a diverse range of roles and sectors, a nationwide voice to express their own biodiversity interests and needs; these were reviewed by an advisor panel to reach consensus on final priorities that reflected the biodiversity outcomes that matter most to stakeholders involved in managing New Zealand's agricultural landscape and the management practices they considered most relevant to achieving those outcomes. This knowledge co‐production process delivered multiple gains that would not have been achieved had a more traditional science‐based process been applied, such as wide stakeholder engagement, identification of a tangible starting point, mitigation of bias or conflict risks, enhanced researcher and practitioner capabilities and a shared understanding of the opportunities and challenges for future development. Institutes addressing conservation challenges within local contexts need to: be 'boundary‐spanning' to manage cross‐scale influences and enable desired conservation behaviours; plan explicitly for the substantial effort required to overcome existing power hierarchies and facilitate transparent and structured decision processes that deliver social justice; better capture the relational values of nature to more successfully leverage peoples' connection to nature in conservation policies and practices; and incorporate wider environmental (e.g. biosecurity), social, economic and political considerations. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.